Risks differences of HIV infection between injection drug users in Rio de Janeiro and Porto Alegre (Archives of Clinical Psychiatry, 2005)
INTRODUCTION: In Brazil, about 19.000 of HIV cases have been attributed to injection drug use, with the seroprevalence among such samples ranging from 25% to 65%. The aim of this study is to compare drug using and HIV risk behaviors among injection cocaine users in Rio de Janeiro and Porto Alegre. METHODS: Comparative analysis of cross-sectional data from two studies conducted in Porto Alegre and Rio de Janeiro. 250 respondents who reported using cocaine by injection in the six months prior to interview were interviewed using NIDA´s RBA (Risk Behavior Assessment) and participated in voluntary HIV testing. RESULTS: There were no statistically significant differences between the two samples in terms of demographic characteristics, with the exception of mean age (31 years in Rio de Janeiro and 28 years in Porto Alegre). The Porto Alegre sample reported more frequent cocaine injection and more injecting risk behaviors. The Rio de Janeiro sample displayed more sexual risk behaviors and more frequent use of both alcohol and snorted cocaine. DISCUSSION: Cocaine injectors in the two regions studied displayed different levels of HIV risk behaviors, and these behaviors appear to be related to the type, method and frequency of drug use. These data were collected between 1994 and 1997 when the use of crack was less common in these cities, which may have changed the current level of risk behaviors for HIV among cocaine users.